(untitled) (JOURNAL OF ADVANCES IN MATHEMATICS, 2015)
Developing methods to design controller which at least under the situation that error exists, could continue its control procedure by decreasing operation till system attains secure situation to eliminate error, is a necessary need in a lot of industrial systems. Therefore designing error tolerable controller for industrial systems by using of bond graph theory to avoid physical and financial damages is one of the most important discussing issues in control engineering and related sciences. Based on this, in this paper we would model the system and error by using of bond graph theory and designing error tolerable controller.